2018
DOI: 10.1002/sce.21449
|View full text |Cite
|
Sign up to set email alerts
|

The roles of social influences on student competence, relatedness, achievement, and retention in STEM

Abstract: Students' perceptions of competence and relatedness are known to influence learning processes and achievement, and may have particular import for underrepresented science, technology, engineering and mathematics (STEM) learners. Sources of social support that contribute to undergraduate life science learners' perceived competence and relatedness were examined, as were achievement and retention outcomes influenced by these sources of support and selfdetermination theory components. Female, ethnically underrepre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 35 publications
4
46
0
1
Order By: Relevance
“…These studies that foreground racism as a specific sociocultural dynamic in African American STEM career attainment help to further explain studies like Hilts et al () that examine sociocultural dynamics in general. They give insight as to why mentoring relationships, or isolation might impact African American STEM aspirants differently than their peers, despite the fact that both African American and non‐African American STEM aspirants might share the same educational space.…”
Section: Literature Reviewmentioning
confidence: 70%
See 1 more Smart Citation
“…These studies that foreground racism as a specific sociocultural dynamic in African American STEM career attainment help to further explain studies like Hilts et al () that examine sociocultural dynamics in general. They give insight as to why mentoring relationships, or isolation might impact African American STEM aspirants differently than their peers, despite the fact that both African American and non‐African American STEM aspirants might share the same educational space.…”
Section: Literature Reviewmentioning
confidence: 70%
“…These studies that foreground racism as a specific sociocultural dynamic in African American STEM career attainment help to further explain studies like Hilts et al (2018) that examine sociocultural dynamics in general.…”
Section: Racism In Stem Career Attainmentmentioning
confidence: 92%
“…Self-confidence has been identified major factor in persistence of underrepresented groups [16], [21]. Students from underrepresented groups primarily derive their perceived competence from contact with classmates [6]. Thus, the psychological/emotional support from mentoring can increase selfconfidence and professional identity [22].…”
Section: Survey Resultsmentioning
confidence: 99%
“…In 2009, 55% of students who started college with a declared STEM major either changed majors or left without earning a degree [4]. By 2018, only 53% of declared engineering majors obtained an engineering degree after six years [ 5]; with attrition being higher for underrepresented groups [6]. An in-depth literature review by Gesinger and Raman [7] reported the key factors of attrition in engineering disciplines to be classroom and academic climate, grades and conceptual understanding, self-efficacy and self-confidence, high school preparation, interest and career goals, and race and gender.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Bureau of Labor Statistics, women make up only 15.9% of the total engineering and architecture workforce (Employed Persons by Detailed Occupation, Sex, Race, and Hispanic or Latino Ethnicity, 2019). This creates an issue, as STEM peer contact correlates with STEM retention among females (Hilts, Part & Bernacki, 2018). Further, according to the Bureau of Labor Statistics, whites make up 79.3% percent of the total engineering and architecture workforce (Employed Persons by Detailed Occupation, 2019).…”
Section: Introductionmentioning
confidence: 99%